2021
DOI: 10.3847/1538-4357/abb3c2
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Auroral Observations Indicating a Major Solar–Terrestrial Storm in 1680: Implication for Space Weather Events during the Maunder Minimum

Abstract: The Maunder Minimum (MM; 1645–1715) is currently considered the only grand minimum within telescopic sunspot observations since 1610. During this epoch, the Sun was extremely quiet and unusually free from sunspots. However, despite a reduced frequency, candidate aurorae were reported in the mid-European sector during this period and have been associated with occurrences of interplanetary coronal mass ejections (ICMEs), although some of them have been identified as misinterpretations. Here, we have analyzed rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 117 publications
(149 reference statements)
1
6
0
Order By: Relevance
“…In this paper, we offer a global analysis of the 12 May 2021 geomagnetic storm, which represents a great space weather event occurring a few years after a new solar cycle onsets. We want to highlight here that despite statistical studies showed that strong geomagnetic storms take place around the maximum and in the declining phase of solar cycles (Meng et al., 2019, and reference therein), even under quiet Sun conditions significant space weather events can occur (Garcia & Dryer, 1987; Hayakawa et al., 2020; Hayakawa, Schlegel, et al., 2021; Willis & Stephenson, 2000). So the 12 May 2021 represents a significant case whose global analysis could help the current understanding about the direct link between solar driver and the relative geomagnetic response.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this paper, we offer a global analysis of the 12 May 2021 geomagnetic storm, which represents a great space weather event occurring a few years after a new solar cycle onsets. We want to highlight here that despite statistical studies showed that strong geomagnetic storms take place around the maximum and in the declining phase of solar cycles (Meng et al., 2019, and reference therein), even under quiet Sun conditions significant space weather events can occur (Garcia & Dryer, 1987; Hayakawa et al., 2020; Hayakawa, Schlegel, et al., 2021; Willis & Stephenson, 2000). So the 12 May 2021 represents a significant case whose global analysis could help the current understanding about the direct link between solar driver and the relative geomagnetic response.…”
Section: Introductionmentioning
confidence: 94%
“…As a closing comment, we want to highlight that despite the Sun is in general more active during its maximum and declining phases, recent papers showed the occurrence of extreme space weather events close to the solar activity minimum (Hayakawa et al, 2020;Hayakawa, Schlegel, et al, 2021;Piersanti et al, 2020). As a consequence, we remark that this kind of global analysis -namely, the study of an ICME propagation from its source on the Sun across the magnetosphere-ionosphere system to its impact in terms of magnetic field changes and magnetospheric particle redistribution, is still the straightforward way available to understand the complex dynamics of the processes occurring in the circumterrestrial environment from a space weather point of view.…”
mentioning
confidence: 99%
“…In this paper, we offer a global analysis of the 12 May 2021 geomagnetic storm, which represents a great space weather event occurring a few years after a new solar cycle onsets. We want to highlight here that despite statistical studies showed that strong geomagnetic storms take place around the maximum and in the declining phase of solar cycles (Meng et al, 2019, and reference therein), even under quiet Sun conditions significant space weather events can occur (Garcia & Dryer, 1987;Hayakawa et al, 2020;Hayakawa, Schlegel, et al, 2021;Willis & Stephenson, 2000). So the 12 May 2021 represents a significant case whose global analysis could help the current understanding about the direct link between solar driver and the relative geomagnetic response.…”
mentioning
confidence: 93%
“…This grand minimum has served as a benchmark for long-term solar variability with a significant reduction in sunspot occurrence (Usoskin et al, 2015;Muñoz-Jaramillo and Vaquero, 2019) and apparent loss of solar coronal streamers (Riley et al, 2015;Hayakawa et al, 2020c). A significant decrease in auroral visibility in the European sector was significant given the high magnetic latitude of this sector during this time period, which would generally cause one to expect more frequent auroral sightings (e.g., Usoskin et al, 2015;Hayakawa et al, 2020d).…”
Section: Introductionmentioning
confidence: 99%